The measure of civilisation : how social development decides the fate of nations - Morris, I Ian Morris (London : Profile books, 2013)
The Measure of Civilization presents a brand-new way of investigating these questions and provides new tools for assessing the long-term growth of societies. Using a groundbreaking numerical index of social development that compares societies in different times and places, award-winning author Ian Morris sets forth a sweeping examination of Eastern and Western development across 15,000 years since the end of the last ice age. He offers surprising conclusions about when and why the West came to dominate the world and fresh perspectives for thinking about the twenty-first century.
Includes bibliographical reference and index